2019
DOI: 10.3233/jad-190572
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Traumatic Brain Injury in a Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is the leading cause of dementia worldwide, affecting over 10% of the elderly population. Epidemiological evidence indicates that traumatic brain injury (TBI) is an important risk factor for developing AD later in life. However, which injury-induced processes that contribute to the disease onset remains unclear. The aim with the present study was to identify cellular processes that could link TBI to AD development, by investigating the chronic impact of two different injury models, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…The severity of a TBI pathogenesis may range from "mild" with a slight change in mental status or consciousness to "severe" with unconsciousness or amnesia after the brain injury. The acute and chronic effects of brain injuries vary significantly from person to person or in animal models of TBI [3,4]. Therefore, no two TBIs are the same with reference to the neuroimmune response and disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of a TBI pathogenesis may range from "mild" with a slight change in mental status or consciousness to "severe" with unconsciousness or amnesia after the brain injury. The acute and chronic effects of brain injuries vary significantly from person to person or in animal models of TBI [3,4]. Therefore, no two TBIs are the same with reference to the neuroimmune response and disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Astrogliosis is also characterized by the upregulation of intermediate filament proteins, and by the secretion of inflammatory mediators and growth factors. GFAP upregulation under pathological conditions has readily been observed in vivo 32 , 65 , 73 76 . We assessed GFAP protein expression in our model system and observed wide heterogeneity between cells, which is also commonly observed in vivo 77 .…”
Section: Discussionmentioning
confidence: 99%
“…A time-course study has revealed that about 60% of synapses are lost in hippocampal CA1 at 2 days post-injury; the synapses are increased to ~ 75% of pre-injury levels 60 days after TBI [ 63 ]. It has been shown that the synaptophysin expressing synapses in the hippocampus are significantly increased 24 weeks, but not 12 weeks, after TBI in a mouse model of Alzheimer’s disease [ 87 ], suggesting a delayed reaction of synaptogenesis after TBI. Our data demonstrate that both the excitatory (PSD-95 positive) and inhibitory (Gephyrin positive) synapses in both the contralateral and ipsilateral hippocampal CA1 are significantly increased at 12 months post-severe TBI as compared with the sham controls, indicating massive synaptogenesis occurring in the hippocampus during the chronic phase of severe TBI.…”
Section: Discussionmentioning
confidence: 99%